Vakarų Lietuvos kapinynų laidosenos ypatumai vėlyvuoju romėniškuoju laikotarpiu - Banytė-Rowell, Rasa (Archaeologia Lituana, 2001)
In his description of the Aestii in Germania Tacitus makes the important observation that the customs of the Aestian tribes are related to those of the Svebii. In practical and even aesthetic matters ethno-culturally different communities change more easily than they can adopt a new custom. Thus the appearance of the same burial trends in various groups of funerary sites is very interesting, because in burial practice ideas are not necessarily adopted for material advantage or aesthetic charm. It is known that there are spatial and temporal differences between the customs, folklore of different peoples or even among tribes of the same ethnic origin. The development of these specifics is also different. In their research of Barbaricum in Roman-age Europe, archaeologists look for the influence of Roman ideas on funerary rites and in southern areas they seek Sarmatian influences. Of equal interest in the search for translation of ideas in funerary practice from one barbarian tribe to another. The aim of this article is to draw attention to certain aspects of burial rites in stone circles in the grave sites of (what is now) Western Lithuania. These aspects could be regarded as common to the region. Most evidence is taken from the graves of Baičiai/Baitai (formely Baiten) in the Klaipėda District. These date from the second half of the Old Iron Age (or the later Roman Age). In graves in this area stones often do not only surround the area of the burial pit but also lie on top of the pit, on its in-fill or base. Investigation of grave goods in Baitai has shown that in the end of the Old Iron Age the method of placing stones in the pit ore above it has quite varied. In the middle of “classical” (circular or oval) stone rings single stones were placed (e.g. child’s grave 9) or a layer of several stones was set down; often reaching the bottom of the pit. Thus in Baitai woman’s grave 24 (ill. 1) a compact stone floor covers the area of the pit contours, covering all except the place reserved for the top of the head. Stones covered a depth of 0.35–0.70 m, reaching the bottom of the pit. Similarly a great part of the pit-infill of Grave 31 comprices stones of various size which do not form a complete base on the level marking the top of the grave pit (ill. 2) . However, in a depth of 50–65 cm the base “spread out” across the whole area of the pit. A part of the small decorations of the horse or corpse were pressed down by the stones or fell among them. The teeth of the person and 2 horses which were sacrificed in his honour spread over quite a wide area at varying depths. These “variations” in laying down stones were in use at more or less the same time since the chronology of graves investigated hitherto in Baitai is not broad (the end of C2 and the C3 period). However, examining material from other stone circle graves in Western Lithuania, we notice that the irregular covering in the middle of the pit floor with stones or the casting of stones into the burial pit, thereby more or less weighing down the corpse, is typical of the later stages of grave use. Changes in the ways of using stones as grave equipment over the Roman period is noticeable in Ugro-Finnish graves in Estonia, where burials with stones took place from the Bronze Age to the late Iron Age. In Tarand graves on the end of the fourth century we note a degeneration in Tarand stone constructions – stones from the grave walls begin to differ slightly from other stones, the dead are buried in the middle or in the edge of earlier Tarands. Having examined available Scandinavian material the author notes the possible hypothesis that in the end of the period “traditional” stone layers above the grave pit, inherited from earlier periods began to disappear everywhere. Perhaps this process took place at the same time as the gradual dissapperance of the barrow tradition in certain areas of Jutland and Scandinavia. In archeological material from the Sambian peninsula we also notice during the late phases of Dollkeim–Kovrovo culture that barrows disapear and more stone-floor graves appear. Thus in all Northern Baltic graves in the Roman period we find the gradual decline of earlier “grandiose” and “ideal” stone form constructions (such as large barrows with accurately – laid concentric stone circles-bases or carefully laid massive stone boxes (bearing in mind primarily those regions where such stone constructions were built before the Roman period). In graves in Western Lithuania we note that in the course of time the form of grave equipment becomes “personalised” for each corpse (see stones’ setting form in Baitai Grave 3: ill. 3), surrounding the grave with a separate ring or joining it to another. This study also examines several other aspects of stone circle grave burials in Western Lithuania which are to be found in the Baitai graves site; viz. the use of layers of branches/stakes and clay in grave pits and the dual-layer burial of corpses. However in Baitai Grave 30 marks of wooden stakes or branches are highlighted by blackered sand (ill. 2, below). It is difficult to tell whether these stakes, similar to branches of trees or bushes, were laid down by the grave pit as a base for the circle or covered the pit. The fact that it was not uncommon for such ordinary material as branches, twigs to be used for grave construction is shown by the exceptionally rich grave goods of a woman’s grave, dated AD. 300 in Sweden (Tuna/Badelunda in Västmanland). The bottom of this grave pit was covered with a layer of twigs. On this “bedding” lay a wooden box-staped coffin or a wooden stand/platform with a covering of thick planks above the pit. A similar form of pit construction was noted in Rostołty – type barrows, which spread across the Narew area (in what are now the Polish wojewodstwa of Białystok and Bielsk). Clay is used in constructing grave pits in Baitai in two ways, like in the Marvelė grave site (Central Lithuanian grave site group) – to frame the grave pit (see ill. 1, Baitai Graves 22-22A,26) and in separate pieces (see ill. 4 Bailai Grave 38). The “strengthening” of the grave pit with clay is also to be found in the Dauglaukis site (Nemunas area). In graves of the Sambia/Nadrovia cultural groups too there are examples of the special use of clay. This article draws special attention to Baitai grave 38–38A whose finds incline one to think that 2 corpses were buried here. Since skeletal remains are almost not found from this grave site of uncremated burials, most often the position of the corpse is estimated from the form of the pit and the position of grave goods. The supposition that at last 2 corpses were buried in Grave 38–38A the pit (with an orientation of 25° NE–205° SW) is conformed not so much by the unusualy long, quite narrow (3.4–3.5 x 0.8–0.9 m) pit or its uneven depth and differing intensity of its burned sand, as by the fact that the human teeth found in the southern end of the pit and fragments of finger bone near brass rings in the middle near the pit could not, anatomically, belong to the same person – they are separated by a distance of approximately 1.15 m (ill. 4). The wires – elements of clothing decoration found near the teeth are more typical of women’s graves. Therefore we suppose that in the southern / sourth western end of the pit a female corpse was interved. She would have been buried partly above the other corpse, remnants of whose fingers were found near the rings. If skythe and glass bead found at the northern end of the pit and were placed there for the corpse-owner of the rings, then we should assume that the “Iower” burial was male. In Lithuania archeological material several skeletal graves from the second half of the Old Iron Age where one body was buried above another have been found among the barrows of the Marvelė grave site, and the graves site at Kalniškiai. Although they are not common, similar “2-storey” double burials are found during the Roman period in that areas of the European Barbaricum. According to material available to the Author, such graves are found in Poland (Vistula river basin and in Masłomęcz culture group), the Scandinavian peninsula and Gotland. Two or even more corpses buried in one pit are regarded by reserches as an effect of various disasters or epidemics. The Polish archeologist A. Kokowski thinks that the burial of the remains of women and children at different times in a common pit (found in Masłomęcz) most likely bears witness to the living tradition of reburying a mother’s remains several times in order with the deaths of her children. A sixth-century Greek historian Procopius described the strange custom of the Herules (a branch of the eastern Goths) for widows to kill themselves (by changing) beside their husband’s grave. Even if such a tradition really did exist among one of the Barbarian tribes it still remains not unclear whether the spouse-suicide was buried in her dead husband’s grave or was burried in a grave dug separately for her. Thus widow-sacrifice can be unrecognisable in archeological sources. The variety of equipment in Baitai graves reveals a similarity of burial custom (in its detail) with more distant areas of the European Barbaricum. Similarity of grave layout does not necessarily indicate ethnic identity. Perhaps this is a part of those customs, on the basis of which, at the end of the first century A.D. Tacitus attributed the Aestian tribe, which researchers identify with the maritime Balts, to the Germanic world.